2021
DOI: 10.1097/md.0000000000025344
|View full text |Cite
|
Sign up to set email alerts
|

Extensive analysis of the molecular biomarkers excision repair cross complementing 1, ribonucleotide reductase M1, β-tubulin III, thymidylate synthetase, and topoisomerase IIα in breast cancer

Abstract: Excision repair cross complementing 1 ( ERCC1 ), ribonucleotide reductase M1 ( RRM1 ), β-tubulin III ( TUBB3 ), thymidylate synthetase ( TYMS ), and topoisomerase IIα ( TOP2A ) genes have been shown to be associated with the pathogenesis and prognosis of various types of carcinomas; however, their roles in breast cancer have not been fully validated. In this study, we evaluated the correlations am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In a recent work, it was shown that the expression levels of ERCC1 , TYMS, and TOP2α were significantly associated with clinical and pathological parameters: menopausal status, tumor size, lymph node metastasis, hormone receptor status, triple-negative status, Ki-67 index, and epidermal growth factor receptor [ 31 ]. With respect to ERCC1 gene, the higher intensity was significantly related to T 1 tumor (mean rank: 64.79 > 42.26, p < 0.001), ER-positive (mean rank: 54.98 > 37.41, p = 0.002), PR-positive (mean rank: 58.35 > 39.05, p < 0.001) and Ki-67 < 20% (mean rank: 66.00 > 44.30, p = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent work, it was shown that the expression levels of ERCC1 , TYMS, and TOP2α were significantly associated with clinical and pathological parameters: menopausal status, tumor size, lymph node metastasis, hormone receptor status, triple-negative status, Ki-67 index, and epidermal growth factor receptor [ 31 ]. With respect to ERCC1 gene, the higher intensity was significantly related to T 1 tumor (mean rank: 64.79 > 42.26, p < 0.001), ER-positive (mean rank: 54.98 > 37.41, p = 0.002), PR-positive (mean rank: 58.35 > 39.05, p < 0.001) and Ki-67 < 20% (mean rank: 66.00 > 44.30, p = 0.001).…”
Section: Discussionmentioning
confidence: 99%